2014
DOI: 10.1089/neu.2013.3241
|View full text |Cite
|
Sign up to set email alerts
|

Early Hemorrhagic Progression of Traumatic Brain Contusions: Frequency, Correlation with Coagulation Disorders, and Patient Outcome: A Prospective Study

Abstract: The focus of this paper is to identify and quantify risk factors for early hemorrhagic progression of brain contusions (HPC) in patients with traumatic brain injury (TBI) and to evaluate their impact on patients' outcome. Further, based on abnormal values in routine blood tests, the role of trauma-induced coagulopathy is analyzed in detail. Therefore, a prospective study of 153 TBI patients was completed at one institution between January 2008 and June 2012. The collected data included demographics, initial Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 31 publications
2
91
0
2
Order By: Relevance
“…This study found a higher proportion of PHI in the coagulopathy group than in the no-coagulopathy group (54% vs. 33%) (OR of 2.4 (95% CI 0.8-8.0)) which is comparable to other studies [1,18]. Despite the heterogenic definition and cutoff values used, the majority of studies have linked coagulopathy with an increased risk of PHI [1,7,18,20,26], although some studies report no relation between PHI and coagulopathy (i.e., unchanged additional CT scans in patients with coagulopathy after TBI) [19,29]. Naturally, part of the PHI is explained by the severity of the primary brain injury more so than by secondary PHI, induced by (unrecognized) coagulopathy.…”
Section: Discussionsupporting
confidence: 84%
“…This study found a higher proportion of PHI in the coagulopathy group than in the no-coagulopathy group (54% vs. 33%) (OR of 2.4 (95% CI 0.8-8.0)) which is comparable to other studies [1,18]. Despite the heterogenic definition and cutoff values used, the majority of studies have linked coagulopathy with an increased risk of PHI [1,7,18,20,26], although some studies report no relation between PHI and coagulopathy (i.e., unchanged additional CT scans in patients with coagulopathy after TBI) [19,29]. Naturally, part of the PHI is explained by the severity of the primary brain injury more so than by secondary PHI, induced by (unrecognized) coagulopathy.…”
Section: Discussionsupporting
confidence: 84%
“…In clinical scenarios, 35–50% of patients with severe TBIs demonstrate progression over the initial 24 hours, therefore it is plausible that the short time course for this study prevented observations of progression. (28, 29) Similarly, clinical studies of TBI victims emphasize that a lack of early radiographic progression is not predictive of outcomes. (3032) Yet, elevated ICP is strongly associated with a fatal outcome following head trauma even when CPP is adequate.…”
Section: Discussionmentioning
confidence: 99%
“…Significant heterogeneity was present in this meta-analysis due to several factors. 11 Prospective observation study GCS <13 and positive head CT scan Joseph et al 12 Retrospective cohort Any GCS level and positive head CT scan Juratli et al 13 Prospective observation study Any GCS level and positive head CT scan Yuan et al 14 Retrospective cohort Any GCS level and positive head CT scan Allard et al 15 Subgroup post hoc analysis of RCT for hypertonic resuscitation for TBI GCS 8 positive head CT scan White et al 16 Prospective cohort Any GCS level and positive head CT scan Yadav et al 17 Prospective cohort Any GCS level and positive head CT scan Kaups et al 18 Retrospective cohort Severe TBI (AIS > 3) Sanus et al 19 Retrospective cohort Any GCS level and positive head CT scan Oertel et al 20 Retrospective cohort Any GCS level and positive head CT scan Stein et al 21 Retrospective cohort GCS < 13 Stein et al 22 Retrospective cohort GCS < 13 TBI, traumatic brain injury; GCS, Glasgow Coma Score; CT, computed tomography; RCT, randomised control trial. There was some variation in the size of the studies (range 46-540); however, the meta-analysis was not heavily weighted by one particular study.…”
Section: Discussionmentioning
confidence: 99%